Versatility of peroxisomes: An evolving concept. Issue 2 (April 2017) - Deb, Rachayeeta; Nagotu, Shirisha
Graphical abstract: Peroxisomes are indispensable organelles present in most eukaryotic cells. Studies on peroxisomes in different model systems like fungi, plants, mammals, trypanosomatids, drosophila, etc. have identified many proteins required for peroxisome biogenesis and have highlighted the unprecedented functions they carry out in various organisms. Peroxisomes co-operate intricately with several other organelles in the cell to carry out various functions and are indispensable for human health. Highlights: Peroxisomes perform multiple functions which are dependent on cell type and environment. ROS production and scavenging and β-oxidation of fatty acids are the most conserved functions across organisms. Several novel functions emphasize a major role for peroxisomes in human health. Abstract: Research spanning almost 50 years has highlighted unique characteristics and irreplaceable list of diverse functions performed by peroxisomes in various model systems. Peroxisomes are single membrane bound highly dynamic organelles ubiquitous to most eukaryotic cells. Proliferation by division of pre-existing organelles and the role of endoplasmic reticulum in the biogenesis of these organelles is now well established. The earliest identified conserved functions of peroxisomes are β-oxidation of fatty acids and reactive oxygen species metabolism. Several studies over the last few decades have reported the importance of this organelle and its numerous cell type, tissue and environment-dependent functions. Their role in several aspects of human health and disease is now under investigation. Studies related to peroxisome biology and functions are now also extended to diverse model systems like Drosophila melanogaster, trypanosomatids, etc. Peroxisomes also intricately collaborate and carry out these functions together with several other organelles in a cell. In this review, we aim to present an overview of our current knowledge of the repertoire of functions of peroxisomes in various model systems.